Molecular detection of pathogens in negative blood cultures in the Lao People’s Democratic Republic - Ter, SK; Rattanavong, S; Roberts, T; Sengduangphachanh, A; Sihalath, S; Panapruksachat, S; Vongsouvath, M; Newton, PN; Simpson, AJH; Robinson, M (American Society of Tropical Medicine and Hygiene, 2021)
Bloodstream infections cause substantial morbidity and mortality. However, despite clinical suspicion of such infections, blood cultures are often negative. We investigated blood cultures that were negative after 5 days of incubation for the presence of bacterial pathogens using specific (Rickettsia spp. and Leptospira spp.) and a broad-range 16S rRNA PCR. From 190 samples, 53 (27.9%) were positive for bacterial DNA. There was also a high background incidence of dengue (90/112 patient serum positive, 80.4%). Twelve samples (6.3%) were positive for Rickettsia spp., including two Rickettsia typhi. The 16S rRNA PCR gave 41 positives; Escherichia coli and Klebsiella pneumoniae were identified in 11 and eight samples, respectively, and one Leptospira species was detected. Molecular investigation of negative blood cultures can identify potential pathogens that will otherwise be missed by routine culture. Patient management would have been influenced in all 53 patients for whom a bacterial organism was identified, and 2.3–6.1% of patients would likely have had an altered final outcome. These findings warrant further study, particularly to determine the cost–benefit for routine use, ways of implementation, and timing of PCR for organisms such as Rickettsia and Leptospira, which are important pathogens in rural Asia.